Ten years of NovoMix 30 in Russian and international clinical practice - Elena Viktorovna Surkova (Сахарный диабет)
Insulin treatment for type 2 diabetes mellitus is challenging in elderly people. Biphasic insulin preparations technically simplify this task, but also increase compliance and facilitate the achievement of therapeutic goals.